Implementasi Informasi Portofolio Pada Marketplace Grafis Tradisional (Gambar Tangan) - Nofiyati Rahman; Dadang Iskandar; Zikri Kurniawan (STMIK Budi Darma, 2020)
Advances in information technology are currently very influential in various fields of life, such as education, economics, and social. The public is demands to be able to use information technology to support their activities by utilizing websites as digital media to be able to reach wider marketing through online media. The traditional graphic creators community of Krigan Purwokerto is currently still doing buying and selling works and displaying their works manually so need a system is able to provide the place for creators to display their works and at the same time be able to handle the process of buying and selling works between creators and clients. The purpose of this research is to make portfolio information in the marketplaces especially traditional graphic creators (hand drawings) to be able to reach wider marketing and build brand by providing Creator portfolio information. The method used in this research is the waterfall method and using the PHP programming language and MySQL database. To involve the results of implementing portfolio information in the traditional graphic creator marketplace can increase the creator's value and rating as showed by an increase in the number of followers and can also recommend his work to prospective buyers in the transaction process of traditional graphic creator works